Dairy-derived saturated fats were not associated with risk of type 2 diabetes mellitus and metabolic syndrome: Tehran Lipid and Glucose Study - Zahra Gaeini; Parvin Mirmiran; Sevda Alvirdizadeh; Fereidoun Azizi (Diabetology & Metabolic Syndrome)
Abstract Emerging evidence indicates that the health effects of saturated fatty acids (SFA) may differ depending on the food source from which they are derived. We aimed to determine the association between dairy-derived SFA and the risk of type 2 diabetes mellitus (T2DM) and metabolic syndrome (MetS). This research was carried out in the Tehran Lipid and Glucose Study, a cohort study of 2256 T2DM-free adults and 1713 MetS-free adults. Adjusted hazard ratios and 95% confidence intervals of T2DM and MetS were calculated in tertile categories of dairy-derived SFA. The risk of T2DM and MetS was estimated through multivariable Cox regression to substitute dairy-derived SFA with other sources of SFA. Participants in the second tertile of dairy-derived SFA had a higher risk of T2DM (HR = 1.59, 95% CI = 1.14–2.21); however, the association did not remain significant in the third tertile (P for trend = 0.082). There were no associations between dairy-derived SFA and the risk of MetS. Substituting dairy-derived SFA for other dietary sources of SFA was not related to the risk of T2DM or MetS. The association between dairy-derived SFA and the risk of T2DM and MetS is still an ongoing research topic. When making dietary choices, it is advisable to consider an overall balanced diet and lifestyle factors.